2023
DOI: 10.1039/d2ob02012b
|View full text |Cite
|
Sign up to set email alerts
|

Cyrene: a bio-based solvent for the Mizoroki–Heck reaction of aryl iodides

Abstract: The development of greener and more sustainable methods, as well as the adaptation of already existing protocols to more environmentally friendly procedures, has become crucial for Organic Synthesis. The introduction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Stini et al reported that Cyrene could be easily recovered after the Mizoroki–Heck reaction by diluting the Cyrene-containing filtrate with water. 20 Ethyl acetate was then added to the mixture forming an organic layer. After removing the organic layer, Cyrene could be recovered from the aqueous layer by evaporating the water, resulting in a recovery yield of 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Stini et al reported that Cyrene could be easily recovered after the Mizoroki–Heck reaction by diluting the Cyrene-containing filtrate with water. 20 Ethyl acetate was then added to the mixture forming an organic layer. After removing the organic layer, Cyrene could be recovered from the aqueous layer by evaporating the water, resulting in a recovery yield of 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Among different organic transformations, Heck crosscoupling reaction (HCR), also known as Mizoroki-Heck reaction, [1][2][3][4][5][6] has received significant interest due to its ability to form C-C bond formation in recent years. Indeed, these reactions have emerged as an efficient replacement, working under mild conditions, for Grignard reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Among different organic transformations, Heck cross-coupling reaction (HCR), also known as Mizoroki–Heck reaction, 1–5 has received significant interest in recent years due to its ability to form C–C bonds. Indeed, this reaction has emerged as an efficient replacement, working under extensively mild conditions, for the Grignard reagents and subsequent required organic transformations to construct CC bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting ppb level of Pd content in the isolated product is beneficial for pharmaceutical research, and the value is comparable with previous results of Pd catalyzed reactions performed in other excellent green solvents, such as γ-valerolactone (GVL) 26 and Cyrene. 27 Next, we studied the Sonogashira-coupling of vinyl iodide 1a with phenylacetylene (4a) in rhamnolipid solution using 1000 ppm Pd(PPh 3 ) 2 Cl 2 as the catalyst, and KOH as the base, and we found complete conversion after 3 hours at 60 °C (Table 2, entry 1). 23 Lowering the concentration of the surfactant gave a lower conversion (47%; entry 3), and in the absence of rhamnolipid the reaction does not take place (Table 2, entry 2).…”
mentioning
confidence: 99%
“…The resulting ppb level of Pd content in the isolated product is beneficial for pharmaceutical research, and the value is comparable with previous results of Pd catalyzed reactions performed in other excellent green solvents, such as γ-valerolactone (GVL) 26 and Cyrene. 27…”
mentioning
confidence: 99%